2020
DOI: 10.1002/er.5373
|View full text |Cite
|
Sign up to set email alerts
|

Phonon phase stability, structural, mechanical, electronic, and thermoelectric properties of two new semiconducting quaternary Heusler alloys CoCuZrZ (Z = Ge and Sn)

Abstract: For meeting the energy demand, the development of new and novel thermoelectric (TE) materials for power generation is very vital. In this draft, we have theoretically investigated two new quaternary CoCuZrZ (Z = Ge and Sn) Heusler alloys for their structural, mechanical, electronic, and TE properties. In the energy minimization process, the alloys are found to be non-magnetic in the ground state. Based on calculated phonon dispersion curves, formation energy, and elastic constants, we propose that both CoCuZrG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…The HAs are remarkable due to their active role in the spin‐injection devices, 13‐17 spintronic devices and high thermoelectric performance, 18‐20 tunnelling magneto‐resistance, 21‐24 spin filters, 16 giant magneto resistance, 25,26 magnetic sensors, 27 non‐volatile magnetic random access memories, 28,29 electro‐mechanical applications 30 . The extensive theoretical 31‐35 and experimental 36‐40 studies of the HAs have been reported in the literature in context to the thermoelectric applications due to their high power factor and low thermal conductivities.…”
Section: Introductionmentioning
confidence: 99%
“…The HAs are remarkable due to their active role in the spin‐injection devices, 13‐17 spintronic devices and high thermoelectric performance, 18‐20 tunnelling magneto‐resistance, 21‐24 spin filters, 16 giant magneto resistance, 25,26 magnetic sensors, 27 non‐volatile magnetic random access memories, 28,29 electro‐mechanical applications 30 . The extensive theoretical 31‐35 and experimental 36‐40 studies of the HAs have been reported in the literature in context to the thermoelectric applications due to their high power factor and low thermal conductivities.…”
Section: Introductionmentioning
confidence: 99%
“…[54][55][56][57] Therefore, the stability of the bulk GaN with the N-vacancy is calculated by the vacancy formation energy. [58][59][60] The calculated method of vacancy stability is seen by the previous work. 61 We first study the structural stability and crystal structure of the bulk GaN with a unit cell.…”
Section: Resultsmentioning
confidence: 99%
“…To improve the TE figure of merit ZT, the chemical doping is extensively used to modify the n . [93][94][95] It was seen that the SnSe, Sn, Ag, and Cu generally behaves like p-type dopant 53,96 while BiCl 3 act as n-type. 97 In the last 20 years, there has been tremendous advances in exploring TE materials 62,98,99 and laboratory constantly records high values of ZT, for examples Bi2Te3-based compounds, [100][101][102] hole doped crystals 103 and lead chalcogenides.…”
Section: Bulk Materials-alloying/doping Approach For Enhancing Ztmentioning
confidence: 99%